Darbības pasākumu analīze riska ietilpīgā vidē: virtuālo līdzekļu pakalpojumu sniedzēja gadījuma izpēte - Akhmedova, Darya (Latvijas Universitāte, 2024)
At the moment of writing, cryptocurrencies have been in existence for more than a decade. Since its creation, the applications for the use of cryptocurrencies and the types of users adopting this invention have changed dramatically. The pseudo-anonymity guaranteed by the system appealed to those performing a variety of illegal activities. This association with crime led to considerable skepticism towards cryptocurrencies by financial authorities, governments, and the general public. Over the past few years, this outlook has started to change, predominantly because of the interest and substantial investment that was made in this technology by renowned businesses and financial institutions. The lack of trust in the system and the absence of relevant regulations still prevent the large-scale adaptation of cryptocurrencies. The rise of cryptocurrencies’ value on the market and their growing popularity around the world opened many challenges and concerns for business and industrial economics. Despite the existence of regulations and strong worldwide cooperation, there is as yet little established scientific knowledge about the markets for cryptocurrencies and their impact on economies, businesses, and people as well as the applicable methods of monitoring the fast-evolving risks. Cryptocurrencies are increasingly scrutinized by regulators, and the literature on the regulation of cryptocurrencies is emerging. Despite that, there is a scarcity of well-conceived, academically grounded literature on the impact of cryptocurrencies on industry, politics, and economics. For this reason, the present case study report is designed to approach the area of digital assets within the scope of risk management activities, having the precise example of one of the many digital assets service providers. It is expected that having this case study included within the realm of other academic-related literature, the knowledge of cryptocurrency will be broadened and its correlation with risk factors and how to approach them will be understood. As a result, the general opinion will shift from being focused on the harms that cryptocurrency creates, such as easy money laundering and sales of illicit goods to a more nuanced understanding of its potential benefits
Analysis of Operating Measures under the Risk-Intensive Environment: A Case Study of a Virtual Asset Service Provider
Keywords: Vadībzinātne; cryptocurrency; risk management; customer service; decetralization